Thermal Comfort of Woolen Fabrics Depending on Physical Properties - ATMACA, MUSTAFA; CEVİZ, NURAY; YILDIZ, ZEHRA (TAYLOR & FRANCIS INC, 2016)
In this study, thermal comfort properties of woolen fabrics depending on the physical properties have been investigated. Thermal and water vapor resistance of fabrics have been measured by the PERMETEST instrument and air permeability has been investigated in a wind tunnel. The air permeability depends on the shape and value of the pores and inter thread channels, which are dependent on the structural parameters of the fabric. Theoretical model has been used in order to determine the porosity values. Experimental data and regression statistics proved that porosity and other fabric parameters have a very strong influence on thermal comfort property.
Keywords: Air permeability; porosity; thermal resistance; water vapor resistance; wind tunnel; woolen; MECHANICAL-PROPERTIES